Political Ideology, Political Party, and Support for Greater Federal Spending on Environmental Protection in the United States: Evidence from the General Social Surveys, 1993–2018. - Yen, Steven T.; Zampelli, Ernest M. (Review of Policy Research, 2021)
This paper focuses on the effects of political ideology and party affiliation on support for more government spending on environmental protection. Pooled‐sample results show that Liberals (Democrats) are more likely to support higher government spending on environmental protection than Moderates (Independents), who, in turn, are more likely to support higher spending levels than Conservatives (Republicans). The results persist even when we control for respondents' opinions concerning whether the federal government, in general, does too little or too much. When stratifying by party, ideological divisions generally narrow, while stratifying by ideology leads to slightly wider divisions between Democrats and Republicans. Together, these results suggest that when Liberals and Conservatives form opinions about government spending on the environment, party affiliation, to some degree, dampens the effects of ideology. Between 2014 and 2018 the probability of supporting more environmental spending increased, albeit slightly, for all ideologies and parties, but more so for Liberals and Democrats.